Pembentukan Kedewasaan Iman dalam Keluarga Kristen: Studi Pustaka tentang Perbedaan Usia dan Pertumbuhan Rohani - Roy Rikki Tambunan; Tommi Nicolas Simanjuntak; Danang Filemon Nainggolan; Olah Valentino Firdaus Aritonang (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
The formation of spiritual maturity within Christian families is often misunderstood as a result of chronological age or the length of one’s Christian experience. This literature study emphasizes that spiritual maturity is not determined by age, but by a continuous process of faith formation through biblical knowledge, spiritual practices, lifestyle modeling, and character transformation. Using library research methods, this study analyzes primary and secondary literature related to the role of families, stages of faith development, and the collaborative role of the church in spiritual formation. The findings reveal that the family serves as the central foundation of faith formation, requiring the active involvement of parents in Bible reading, prayer, ethical guidance, and moral example. Furthermore, spiritual maturity is influenced by developmental stages that do not necessarily correspond to biological age. The church functions as a collaborative partner that supports family spiritual growth through teaching, ministry involvement, and pastoral guidance. This study concludes that spiritual maturity is reflected in character and actions rather than ritual participation alone, and it recommends strengthening family-based faith education and cooperation with the church as a foundation for authentic spiritual growth.